Regulatory reliance pathways during health emergencies: enabling timely authorizations for COVID-19 vaccines in Latin America - Ivar T. van der Zee; Rick A. Vreman; Lawrence Liberti; Mario Alanis Garza (Pan American Health Organization, 2022)
Objectives. To map the timing and nature of regulatory reliance pathways used to authorize COVID-19 vaccines in Latin America. Methods. An observational study was conducted assessing the characteristics of all COVID-19 vaccine authorizations in Latin America. For every authorization it was determined whether reliance was used in the authorization process. Subgroups of reference national regulatory authorities (NRAs) and non-reference NRAs were compared. Results. 56 authorizations of 10 different COVID-19 vaccines were identified in 18 countries, of which 25 (44.6%) used reliance and 12 (21.4%) did not. For the remaining 19 (33.0%) it was not possible to determine whether reliance was used. Reference agencies used reliance less often (40% of authorizations with a known pathway) compared to non-reference agencies (100%). The median review time was just 15 days and does not meaningfully differ between reliance and non-reliance authorizations. Conclusions. This study demonstrated that for these vaccines, despite reliance pathways being associated with numerous rapid authorizations, independent authorization review times were not considerably longer than reliance reviews; reliance pathways were not a prerequisite for rapid authorization. Nevertheless, reliance pathways provided rapid authorizations in response to the COVID-19 emergency.